Choroid plexus carcinoma in children: The Head Start experience. Issue 5 (8th February 2015) - Zaky, Wafik; Dhall, Girish; Khatua, Soumen; Brown, Robert J.; Ginn, Kevin F.; Gardner, Sharon L.; Yildiz, Vedat O.; Yankelevich, Maxim; Finlay, Jonathan L.
Abstract: Background: Choroid plexus carcinoma (CPC) is a rare aggressive intracranial neoplasm with a predilection for young children and a historically poor outcome. Currently, no defined optimal therapeutic strategy exists. The Head Start (HS) regimens have included irradiation‐avoiding strategies in young children with malignant brain tumors using high dose chemotherapy to improve survival and minimize neurocognitive sequelae. Procedure: Three sequential HS studies have been conducted from 1991 to 2009. HS treatment strategy has consisted of maximal surgical resection followed by five cycles of intensive induction followed by consolidation myeloablative chemotherapy with autologous hematopoietic stem cell rescue (AuHCR). Irradiation was given following recovery from consolidation based on the patient's age and evidence of residual disease. Results: Twelve children with CPC (median age of 19.5 months) have been treated with HS regimens. Ten patients had >95% resection. Three patients had disseminated disease at diagnosis. Ten patients completed consolidation of whom five are alive, irradiation and disease free at 29, 43, 61, 66 and 89 months from diagnosis. Seven patients experienced tumor recurrence/progression at a median time of 13 months (range 2–43 months). Five patients received irradiation, one for residual disease and four upon progression or recurrence, of whom one is alive at 61 months. The 3‐ and 5‐year progression‐free survivals are 58% and 38% and overall survivals 83% and 62% respectively. Late deaths from disease beyond 5 years were also noted. Conclusion: Head Start strategies may produce long‐term remission in young children with newly diagnosed CPC with avoidance of cranial irradiation. Pediatr Blood Cancer 2015;62:784–789. © 2015 Wiley Periodicals, Inc.